Integrating Social and Emotional Learning: Creating Space for Afterschool Educator Expertise. (June 2022) - White, Annie M.; Akiva, Thomas; Colvin, Sharon; Li, Junlei
A growing movement suggests that social and emotional learning (SEL) should be integrated into educational experiences in and outside schools. Afterschool programs can be particularly well suited for SEL, and afterschool educators can play an important role in skill development. We interviewed 23 experienced afterschool educators in community-based programs to understand how staff encourage SEL and how program directors support staff in doing so. Findings show that afterschool educators describe integrating SEL into their daily interactions with children by creating and catching teachable moments. Program directors served either as compliance enforcers or partners who supported staff's autonomy to encourage SEL despite top-down mandates. Findings suggest that educators can develop substantial expertise integrating SEL into their professional work. By recognizing and empowering such expertise, program leaders can support implementation and innovation of SEL practices. Allocating resources toward intentional integration of SEL is an important next step for this work.